A carbon science perspective in 2018: Current achievements and future challenges. (June 2018) - Bianco, Alberto; Chen, Yongsheng; Chen, Yuan; Ghoshal, Debjit; Hurt, Robert H.; Kim, Yoong Ahm; Koratkar, Nikhil; Meunier, Vincent; Terrones, Mauricio
Graphical abstract: Image 1